THE INFLUENCE OF WORK-LIFE BALANCE ON EMPLOYEE WELL-BEING MEDIATED BY JOB STRESS : Pengaruh Work-Life Balance terhadap Employee Well-Being melalui Stres Kerja pada PT.Bank Nagari - Farhan Maulana Akbar; Mega Asri Zona (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study examines the influence of work-life balance on employee well-being, with job stress as a mediating variable, focusing on employees of PT Bank Nagari Main Branch. The research uses the Job Demand-Resources Theory to explore these relationships, employing a quantitative approach with 60 respondents selected through proportionate stratified random sampling. Data was analyzed using SmartPLS 4.1.0.2. The results of this study show that: (1) work-life balance positively but insignificantly affects employee well-being, (2) work-life balance has a significant negative effect on job stress, (3) job stress negatively but insignificantly impacts employee well-being, (4) mediation analysis reveals that job stress does not significantly mediate the relationship between work-life balance and employee well-being.